Nutrition in Physical Therapist Practice: Tools and Strategies to Act Now. Issue 5 (15th February 2021) - Berner, Patrick; Bezner, Janet R; Morris, David; Lein, Donald H
Abstract: It has been established that physical therapist practice includes screening for and providing information on diet and nutrition to patients, clients, and the community. Yet, an overwhelming amount of often contradictory diet and nutrition information poses a challenge for physical therapists to identify and maintain knowledge that they can rely on to screen for and discuss these topics with their patients, clients, and community members. The purposes of this perspective paper are to summarize the best known screening tools for general health, diet, and nutrition; provide intervention strategies that can be used to support behavior change related to diet and nutrition; and identify the most relevant resources and approaches from which physical therapist clinicians can build skill in addressing the nutritional needs of patients, clients, and the community.